Impacts of plastic ingestion on post-hatchling loggerhead turtles off South Africa. Issue 1 (15th June 2016) - Ryan, Peter G.; Cole, Georgina; Spiby, Kevin; Nel, Ronel; Osborne, Alexis; Perold, Vonica
Abstract: Twenty-four of 40 (60%) loggerhead turtle Caretta caretta post-hatchlings (carapace < 9 cm) that died within 2 months of stranding on southern Cape beaches in April 2015 contained ingested anthropogenic debris. Plastic comprised of 99% of debris: 77% hard plastic fragments, 10% flexible packaging and 8% fibres; industrial pellets comprised only 3%, compared to ~ 70% in 1968–1973, when 12% of stranded post-hatchlings contained plastics. Turtles selected for white (38%) and blue (19%) items, but translucent items (23%) were under-represented compared to beach mesodebris. Ingested loads did not decrease up to 52 days in captivity, indicating long retention times. Plastic killed 11 turtles by blocking their digestive tracts or bladders, and contributed to the deaths of five other turtles. Our results indicate that the amount and diversity of plastic ingested by post-hatchling loggerhead turtles off South Africa have increased over the last four decades, and now kill some turtles. Highlights: 60% of post-hatchling loggerhead turtles stranded in South Africa contained plastic. The incidence of ingestion and diversity of plastic has increased since the 1970s. Turtles favoured blue and white plastic items, but clear items were under-represented. Turtles retained ingested plastic for up to 2 months in captivity. Plastic ingestion contributed to the deaths of at least 16 of 40 turtles